1988
DOI: 10.1126/science.2454506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Forskolin on Voltage-Gated K + Channels Is Independent of Adenylate Cyclase Activation

Abstract: Forskolin is commonly used to stimulate adenylate cyclase in the study of modulation of ion channels and other proteins by adenosine 3',5'-monophosphate (cAMP)-dependent second messenger systems. In addition to its action on adenylate cyclase, forskolin directly alters the gating of a single class of voltage-dependent potassium channels from a clonal pheochromocytoma (PC12) cell line. This alteration occurred in isolated cell-free patches independent of soluble cytoplasmic enzymes. The effect of forskolin was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
103
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(107 citation statements)
references
References 25 publications
4
103
0
Order By: Relevance
“…Though this response was significantly smaller than without FSK (see Table 4, P<0.05), the combined response to FSK plus isoprenaline was not significantly different from that to isoprenaline alone (P>0.05). Forskolin has also been reported to block potassium channels (Hoshi et al, 1988;Cook, 1988), and this might be the origin of the complex influence of FSK.…”
Section: Hyperpolarization Is Mediated Via the F2-adrenoceptormentioning
confidence: 99%
“…Though this response was significantly smaller than without FSK (see Table 4, P<0.05), the combined response to FSK plus isoprenaline was not significantly different from that to isoprenaline alone (P>0.05). Forskolin has also been reported to block potassium channels (Hoshi et al, 1988;Cook, 1988), and this might be the origin of the complex influence of FSK.…”
Section: Hyperpolarization Is Mediated Via the F2-adrenoceptormentioning
confidence: 99%
“…In addition to its ability to increase intracellular levels of cAMP through direct activation of adenylyl cyclase, forskolin has also been shown to affect certain cellular processes through a mechanism that does not involve production of cAMP (Joost and Steinfelder, 1987;Hoshi et al, 1988;Laurenza et al, 1989;Beavo and Reifsnyder, 1990). To determine if the inhibitory effect of forskolin on DNA synthesis is mediated via cAMP, we treated Reh cells with 3-isobutyl-1-methylxanthine (IBMX), cholera toxin (CTX), and 8-CPTcAMP.…”
Section: Inhibition Of Dna Synthesis By Forskolin Is Mediated Via Campmentioning
confidence: 99%
“…Recent reports have shown that the modulation of ion channels and the neurotropic actions of forskolin may be independent of the adenylate cyclase-cyclic AMP system (Hoshi, Garber & Aldrich, 1988;Wagoner & Pallotta, 1988;Wakade et al 1990 b). However, in the present study we establish a direct involvement of cyclic AMP in the modulation of sympathetic transmitter release.…”
Section: Neuronal Blockers Do Not Alter Transmembrane Ca2+ Currentsmentioning
confidence: 99%